2000
DOI: 10.1034/j.1600-0706.2000.910203.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of familiarity on competitive interactions between threespined sticklebacks

Abstract: Utne-Palm, A. C. and Hart, P. J. B. 2000. The effects of familiarity on competitive interactions between threespined sticklebacks. -Oikos 91: 225 -232.In this study, pairs of juvenile sticklebacks either familiar with each other or pairs unfamiliar with each other met to share a food source. The study showed that sticklebacks were less aggressive towards a partner when sharing a common food source with a familiar conspecific, compared to when sharing a food source with an unfamiliar conspecific. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(86 citation statements)
references
References 28 publications
3
82
1
Order By: Relevance
“…Evidence that familiarity leads to reduced aggression has been previously documented for fishes including rainbow trout ( Johnsson 1997), three-spined sticklebacks (Utne-Palm & Hart 2000) and Atlantic salmon (O'Connor et al 2000). Furthermore, low levels of aggression are known to lead to improvements in vigilance, predator detection and survival ( Jakobsson 1987;Brick 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence that familiarity leads to reduced aggression has been previously documented for fishes including rainbow trout ( Johnsson 1997), three-spined sticklebacks (Utne-Palm & Hart 2000) and Atlantic salmon (O'Connor et al 2000). Furthermore, low levels of aggression are known to lead to improvements in vigilance, predator detection and survival ( Jakobsson 1987;Brick 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The putative benefits of preferential association with familiars include improved foraging opportunities (Metcalfe & Thomson 1995), reduced investment in epithelial alarm cells (Wisenden & Smith 1998) and reduced levels of resource competition (Jakobsson 1987;Johnsson 1997;Utne-Palm & Hart 2000). Indirect evidence for an anti-predator function of familiarity-biased association comes from a study of fathead minnows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Losers generally exhibit more pronounced behavioural and physiological (e.g. skin darkening) avoidance responses when faced with familiar opponents (Miklósi et al 1995(Miklósi et al , 1997Morris et al 1995;Johnsson 1997;O'Connor et al 2000;Utne-Palm & Hart 2000), suggesting that individual recognition amplifies the loser effect. Contests between familiar opponents seldom escalate (Keeley & Grant 1993;Earley et al 2003).…”
Section: Individual Recognitionmentioning
confidence: 99%
“…A corollary of this is the gradual decrease in familiarity preferences that occurs if familiar individuals are separated. For example, Utne- Palm & Hart's (2000) study of familiarity in three-spined stickleback revealed a gradual increase in familiarity over a 4-week period of association and a subsequent decrease in familiarity over a 4-week period of isolation. In a study of rainbow trout, Johnsson (1997) found that the separation of pairs of territorial combatants for a period of 3 days was sufficient for the familiarity-biased aggression levels to decay.…”
Section: P Promelasmentioning
confidence: 99%